43‐2: Low Efficiency Attenuation and Stable Monochromaticity for Non‐Polar m‐Plane Micro‐Ligh‐Emitting‐Diodes (Micro‐LEDs). Issue 1 (28th June 2022) - Liu, Yibo; Feng, Feng; Zhang, Ke; Chan, Ka-Wah; Liu, Zhaojun; Kwok, Hoi Sing
Abstract : In this paper, the gallium nitride (GaN) free‐standing non‐polar m‐plane micro‐LEDs and polar c‐plane micro‐LEDs on patterned sapphire substrate with a 550‐nm emission light were fabricated and characterized. Compared with c‐plane micro‐LEDs suffering from strong quantum confined stark effect (QCSE), the absence of polarization effect in m‐plane devices contributed to a lower efficiency attenuation and narrower peak and color shift with elevating current density. Specifically, the peak wavelength shift for c‐plane and m‐plane micro‐LEDs was 11.81 nm and 8.12 nm respectively from 1 to 500 A/cm 2, and the efficiency droop ratio was 50.2% for c‐plane and 27.2% for mplane devices from 0.1 to 300 A/cm 2 . Importantly, our m‐plane micro‐LEDs achieved a stable monochromaticity and wider color gamut under different injection current density (97.9% and 98.2% of Rec. 2020 at 1 and 500 A/cm 2 ).